Method for improving acidolysis performance of titanium concentrate and titanium dioxide preparation method

By performing ore dressing and continuous acid decomposition of titanium concentrate, the preheated waste acid is used to induce acid decomposition reaction, which solves the problem that the acid decomposition rate and acid decomposition performance of titanium concentrate in the prior art is difficult to simultaneously improve, and efficient waste acid reuse and quality improvement of titanium dioxide products are achieved.

CN119710298APending Publication Date: 2025-03-28PANZHIHUA IRON & STEEL RES INST OF PANGANG GROUP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411857808.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art cannot simultaneously improve the acid-resolving rate of titanium concentrate and the sedimentation and filtration performance of acid-resolving titanium liquid, and the waste acid reuse efficiency is low.

Method used

By ore dressing the titanium concentrate, the proportion of ilmenite is increased and the proportion of pyroxene and feldspar is reduced. Then, continuous acid decomposition is carried out, and the acid decomposition reaction is used to induce the acid decomposition reaction after preheating, and the acid decomposition rate and waste acid reuse level are improved.

Benefits of technology

The acid-resolving rate of titanium concentrate has been improved, the sedimentation and filtration performance of acid-resolving titanium liquid has been improved, the reuse rate of waste acid has been improved, the production cost has been reduced, and the quality of titanium dioxide products has been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710298A_ABST
    Figure CN119710298A_ABST
Patent Text Reader

Abstract

The invention provides a method for improving the acidolysis performance of titanium concentrate. The method comprises the following steps that S10, the titanium concentrate is provided; s20, the titanium concentrate is subjected to beneficiation treatment, so that the proportion of ilmenite in the titanium concentrate is increased, the proportion of pyroxene and feldspar in the titanium concentrate is reduced, and upgraded titanium concentrate is obtained; and S30, the upgraded titanium concentrate is subjected to continuous acidolysis treatment. According to the method, the purposes of improving the titanium acidolysis efficiency in the titanium concentrate and improving the settling and filtering rate of the acidolysis titanium solution are achieved, and the acidolysis rate of the titanium concentrate and the comprehensive utilization level of the waste acid are further improved in the mode that the acidolysis reaction of the titanium concentrate is efficiently initiated after indirect preheating of the waste acid. The invention also provides a preparation method of the titanium dioxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of titanium dioxide preparation, and specifically relates to a method for improving the acid hydrolysis performance of titanium concentrate. The invention also relates to a method for preparing titanium dioxide powder. Background Art

[0002] Titanium dioxide, as the inorganic pigment with the best whiteness in the world, has good and stable physical and chemical properties and is widely used in coatings, plastics, papermaking, inks, batteries and other fields. Titanium concentrate is the main titanium raw material for sulfuric acid titanium dioxide. Its acid hydrolysis performance is not only directly related to technical and economic indicators, but also to the quality of the final titanium dioxide product. The acid hydrolysis performance of titanium concentrate is the focus of attention of sulfuric acid titanium dioxide manufacturers. In addition, waste acid is one of the key factors restricting the survival and development of sulfuric acid titanium dioxide. How to achieve efficient reuse of waste acid is also the focus of attention of sulfuric acid titanium dioxide manufacturers.

[0003] The acid hydrolysis performance of titanium concentrate includes the acid hydrolysis rate of titanium concentrate, the sedimentation of acid hydrolyzed titanium liquid, and the filtration performance. The higher the acid hydrolysis rate of titanium concentrate, the higher the titanium yield; the better the sedimentation and filtration performance of the acid hydrolyzed titanium liquid, the fewer solid impurity particles in the titanium liquid, the fewer bad crystallization centers in the titanium liquid, the better the quality of the metatitanic acid produced by the hydrolysis of the titanium liquid, and the better the quality of the final titanium dioxide product. The existing technology cannot achieve the purpose of simultaneously improving the titanium acid hydrolysis rate and the sedimentation and filtration performance of the acid hydrolyzed titanium liquid in titanium concentrate, because there is a contradictory relationship between the two. After the titanium acid hydrolysis rate in titanium concentrate is improved, the acid hydrolysis rate of calcium and silicon in the titanium concentrate also increases, and the formed calcium sulfate and silicate colloidal impurity particles also increase accordingly. The colloidal impurity particles usually have a weaker effect on the polyacrylamide flocculant for titanium liquid, the colloidal particles have better stability, and the sedimentation rate is slow. After the titanium liquid is settled, the solid content of the colloidal impurity particles in the titanium liquid is high, and the colloidal substances are easy to block the gaps and holes of the filter cloth on the plate frame used for titanium liquid filtration, making it difficult to filter the titanium liquid.

[0004] In response to the above-mentioned technical defects, sulfuric acid process titanium dioxide manufacturers usually improve the titanium acid hydrolysis rate in titanium concentrate by changing the acid hydrolysis process conditions of titanium concentrate (for example, reaction acid concentration, reaction acid-ore ratio, aging temperature, aging time, premixing time and titanium concentrate particle size). However, due to limitations such as production costs and production efficiency, the titanium acid hydrolysis rate of titanium concentrate in the existing technology generally remains at 96.0% to 97.0%, and the titanium acid hydrolysis rate cannot be further improved.

[0005] In addition, the acid hydrolysis of titanium concentrate for sulfuric acid titanium dioxide in the prior art is intermittent acid hydrolysis and continuous acid hydrolysis. Continuous acid hydrolysis has the advantages of high acid hydrolysis efficiency, good stability and easy tail gas treatment compared with intermittent acid hydrolysis. Therefore, continuous acid hydrolysis of titanium concentrate has become the development direction of sulfuric acid titanium dioxide acid hydrolysis. However, in the process of continuous acid hydrolysis of titanium concentrate, due to the slow reaction rate and low acid hydrolysis rate of titanium concentrate, there is a situation where waste acid cannot induce its efficient acid hydrolysis, and thus waste acid reuse cannot be achieved.

[0006] In summary, there is still much room for improvement in improving the acid hydrolysis performance of titanium concentrate and recycling waste acid. Summary of the invention

[0007] In view of the shortcomings of the prior art, the object of the present invention is to provide a method for improving the acid hydrolysis performance of titanium concentrate. The present invention also relates to a method for preparing titanium dioxide.

[0008] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention provides a method for improving the acid hydrolysis performance of titanium concentrate, the method comprising the following steps: S10. Provide titanium concentrate; S20, performing beneficiation treatment on the titanium concentrate, so that the proportion of ilmenite in the titanium concentrate is increased, and the proportion of pyroxene and feldspar in the titanium concentrate is reduced, so as to obtain an upgraded titanium concentrate; S30, continuously performing acid hydrolysis treatment on the upgraded titanium concentrate.

[0009] In one embodiment, in step S20, The titanium concentrate is beneficiated by flotation process using 98% by mass industrial grade sulfuric acid and collector, wherein the amount of industrial grade sulfuric acid added is 34.0 kg / t to 40.0 kg / t of titanium concentrate, and the amount of collector added is 7.8 kg / t to 9.5 kg / t of titanium concentrate.

[0010] In one embodiment, in step S10, The proportion of ilmenite in the titanium concentrate is <90wt%, the proportion of pyroxene in the titanium concentrate is 3.1wt%, and the proportion of feldspar in the titanium concentrate is 0.8wt%.

[0011] In one embodiment, in step S20, The proportion of ilmenite in the upgraded titanium concentrate is 95.0wt% to 98.0wt%, the proportion of pyroxene in the upgraded titanium concentrate is 0.5wt% to 1.4wt%, and the proportion of feldspar in the upgraded titanium concentrate is 0wt% to 0.3wt%.

[0012] In one embodiment, in step S30, the continuous acid hydrolysis process comprises the following steps: S31, premixing the upgraded titanium concentrate with concentrated sulfuric acid to obtain an acid ore premix; S32, providing waste acid, and preheating the waste acid to obtain preheated waste acid, the waste acid preheating temperature T = -32.24 + 240 × C + (10 ° C ~ 50 ° C), wherein C is the mass concentration of sulfuric acid in the waste acid; S33, mixing the preheated waste acid with the acid-ore premix, initiating a continuous acidolysis reaction with the waste acid, and obtaining an acidolysis solid phase after the reaction, wherein the preheated waste acid is mixed with the concentrated sulfuric acid in step S31 to form a reaction acid.

[0013] In one embodiment, Before step S31, the upgraded titanium concentrate is dried and ball-milled, and the moisture content of the upgraded titanium concentrate after drying is ≤0.5%, and the particle size of the upgraded titanium concentrate is 1% to 3% of the residue on a 325-mesh sieve; In step S31, the mass fraction of concentrated sulfuric acid is 98%; In step S32, the concentration of sulfuric acid in the waste acid is 20 wt% to 60 wt%; In step S33, the mass ratio of the reaction acid to the upgraded titanium concentrate is 1.60-1.62, the concentration of the reaction acid is 83.0wt%-83.5wt%, and the aging time is 1h-3h.

[0014] In one embodiment, in step S32, the waste acid is indirectly preheated by saturated steam, and the temperature of the saturated steam is 140°C to 250°C.

[0015] In one embodiment, after step S33, the following steps are also included: S34, leaching the acid-decomposed solid phase to obtain a leached titanium liquid; S35, reducing the leached titanium liquid with iron powder to obtain a reduced leached titanium liquid; S36. Add a flocculant to the reduced leached titanium solution for sedimentation treatment.

[0016] In one embodiment, In step S34, the concentration of titanium dioxide in the leached titanium solution is 125 g / L to 135 g / L; In step S35, the concentration of trivalent titanium in the leached titanium solution after reduction is 1 g / L to 2 g / L; In step S36, the ratio of the mass of the added flocculant to the mass of titanium dioxide in the reduced leached titanium solution is 0.25‰.

[0017] The present invention also provides a method for preparing titanium dioxide, which includes the method for improving the acid hydrolysis performance of titanium concentrate as described above.

[0018] Compared with the prior art, the beneficial technical effects of the present invention are: The present invention increases the proportion of ilmenite mineral phase in the titanium concentrate and reduces the proportion of pyroxene and feldspar phases by first performing ore dressing on the titanium concentrate, and then performs acid hydrolysis on the quality-improved titanium concentrate obtained after ore dressing, thereby achieving the purpose of simultaneously improving the efficiency of titanium acid hydrolysis in the titanium concentrate and improving the sedimentation and filtration rate of the acid hydrolysis titanium liquid, and reducing the impurity content in the titanium liquid, so that the quality of the final titanium dioxide product is also improved accordingly. In addition, the present invention further improves the titanium concentrate acid hydrolysis rate and the comprehensive utilization level of waste acid by indirect preheating of waste acid to efficiently induce the acid hydrolysis reaction of titanium concentrate, the titanium concentrate acid hydrolysis rate is ≥98.0%, and the waste acid (acid mass fraction is 100%) reuse level is ≥0.286t / t titanium dioxide. The method of the present invention reduces production costs, improves the quality of sulfuric acid titanium dioxide products and the level of waste acid reuse, which has important technical, economic, environmental and social significance. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0020] Figure 1 A schematic flow chart of a method for improving the acid hydrolysis performance of titanium concentrate according to the present invention; Figure 2 Another schematic flow chart of the method for improving the acid hydrolysis performance of titanium concentrate according to the present invention. DETAILED DESCRIPTION

[0021] The following is a further detailed description of the embodiments of the present disclosure in conjunction with the accompanying drawings and examples. The detailed description of the following embodiments and the accompanying drawings are used to exemplarily illustrate the principles of the present disclosure, but cannot be used to limit the scope of the present disclosure. The present disclosure can be implemented in many different forms and is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

[0022] The present disclosure provides these embodiments to make the present disclosure thorough and complete, and to fully express the scope of the present disclosure to those skilled in the art. It should be noted that unless otherwise specifically stated, the relative arrangement of the parts and steps, the composition of the materials, the numerical expressions and the numerical values ​​set forth in these embodiments should be interpreted as being merely exemplary, and not as limiting.

[0023] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0024] like Figure 1 As shown, the present invention provides a method for improving the acid hydrolysis performance of titanium concentrate, the method comprising the following steps: S10. Provide titanium concentrate.

[0025] S20. Performing mineral processing on the titanium concentrate to increase the proportion of ilmenite in the titanium concentrate and reduce the proportion of pyroxene and feldspar in the titanium concentrate, so as to obtain an improved titanium concentrate.

[0026] S30, continuously performing acid hydrolysis treatment on the upgraded titanium concentrate.

[0027] In one embodiment, in step S20, the titanium concentrate is subjected to mineral processing by flotation process and using industrial grade sulfuric acid with a mass fraction of 98% and a collector. The amount of industrial grade sulfuric acid added is 34.0 kg / t titanium concentrate to 40.0 kg / t titanium concentrate, the amount of collector added is 7.8 kg / t titanium concentrate to 9.5 kg / t titanium concentrate, and the collector is butyl xanthate.

[0028] The titanium concentrate of the present invention is a rock ore titanium concentrate, and the titanium concentrate of the present invention is prepared from the iron tailings of vanadium-titanium magnetite as raw material. In one embodiment, in step S10, the proportion of ilmenite in the titanium concentrate is <90wt%, the proportion of pyroxene in the titanium concentrate is 3.1wt%, and the proportion of feldspar in the titanium concentrate is 0.8wt%.

[0029] In one embodiment, in step S20, compared with the proportions of ilmenite, pyroxene and feldspar in the titanium concentrate, the proportion of ilmenite in the upgraded titanium concentrate obtained by flotation is increased to 95.0wt%~98.0wt%, the proportion of pyroxene in the upgraded titanium concentrate is reduced to 0.5wt%~1.4wt%, and the proportion of feldspar in the upgraded titanium concentrate is reduced to 0wt%~0.3wt%.

[0030] It should be understood by those skilled in the art that during the acid hydrolysis of titanium concentrate, titanium, iron, magnesium, manganese, silicon and calcium in the titanium concentrate can be acid hydrolyzed by sulfuric acid and enter the titanium liquid in the form of soluble sulfate or insoluble calcium sulfate and silicate colloidal impurity particles. Since the reaction process is non-selective, the higher the acid hydrolysis rate of titanium in the titanium concentrate, the higher the acid hydrolysis rate of other components. Among them, the calcium and silicon elements in the titanium concentrate are mainly contained in pyroxene and feldspar. As the titanium concentrate is acid hydrolyzed, the calcium and silicon in the pyroxene and feldspar react with sulfuric acid to form calcium sulfate and silicate, respectively. Since calcium sulfate and silicate are colloidal substances, they are easy to adsorb other impurity particles in the titanium liquid to form colloidal particles, which are relatively stable in the titanium liquid and have a slow precipitation rate. When the titanium liquid is filtered and separated by a plate frame, it is easy to block the gaps and holes in the filter cloth on the plate frame, greatly reducing the separation rate of the titanium liquid and the residual solid in the titanium liquid. Since the flocculant itself has limited effect on colloidal substances, increasing the amount of flocculant or selecting other types of flocculants is still difficult to achieve a better sedimentation and filtration effect, which in turn leads to a decrease in the acid hydrolysis performance of titanium concentrate.

[0031] In view of the above technical defects, the present invention first increases the proportion of ilmenite mineral phases in titanium concentrate and reduces the proportion of pyroxene and feldspar phases by ore dressing, so that more than 99% of the titanium in the upgraded titanium concentrate is contained in ilmenite that is easy to acid-lyze, so that titanium is more easily acid-lyzed into the titanium liquid. In addition, after the proportion of pyroxene and feldspar in the titanium concentrate is reduced, the proportion of inclusion and encapsulation of ilmenite is reduced, so that the acid-lysis rate of ilmenite will be further improved. More than 90% of the calcium and silicon elements contained in pyroxene and feldspar are reduced by more than half, and the proportion of calcium and silicon in the titanium concentrate is also reduced by more than half accordingly, and the amount of colloidal calcium sulfate and silicic acid generated by the reaction of calcium, silicon and sulfuric acid will also be reduced by more than half. Therefore, when the upgraded titanium concentrate obtained after ore dressing is subjected to acid-lysis treatment, the sedimentation and filtration rate of the acid-lyzed titanium liquid can be significantly improved. The method of the present invention can achieve the purpose of simultaneously improving the efficiency of titanate acid decomposition in titanium concentrate and improving the sedimentation and filtration rates of acid-decomposed titanium liquid, thereby further improving the titanate acid decomposition rate on the basis of the existing technology.

[0032] In one embodiment, if Figure 2 As shown, in step S30, the continuous acid hydrolysis process includes the following steps: S31, premixing the upgraded titanium concentrate with concentrated sulfuric acid to obtain an acid ore premix.

[0033] S32, providing waste acid, and preheating the waste acid to obtain preheated waste acid, the waste acid preheating temperature T = -32.24 + 240 × C + (10 ° C ~ 50 ° C), wherein C is the mass concentration of sulfuric acid in the waste acid.

[0034] S33, mixing the preheated waste acid with the acid-ore premix, initiating a continuous acidolysis reaction with the waste acid, and obtaining an acidolysis solid phase after the reaction, wherein the preheated waste acid is mixed with the concentrated sulfuric acid in step S31 to form a reaction acid.

[0035] In one embodiment, before step S31, the upgraded titanium concentrate is dried and ball-milled, and the moisture content of the upgraded titanium concentrate after drying is ≤0.5%, and the particle size of the upgraded titanium concentrate is 1% to 3% of the residue on the 325 mesh sieve. In step S31, the mass fraction of concentrated sulfuric acid is 98%. In step S32, the concentration of sulfuric acid in the waste acid is 20wt% to 60wt%. In step S33, the mass ratio of the reaction acid to the upgraded titanium concentrate is 1.60 to 1.62, the concentration of the reaction acid is 83.0wt% to 83.5wt%, and the aging time is 1h to 3h. Those skilled in the art should understand that the mass ratio of the reaction acid to the upgraded titanium concentrate refers to the ratio of the mass of pure sulfuric acid in sulfuric acid to the mass of the upgraded titanium concentrate.

[0036] In one embodiment, in step S32, the waste acid is indirectly preheated by saturated steam, and the saturated steam temperature is 140°C to 250°C. In one embodiment, the waste acid is indirectly preheated by a graphite block heat exchanger, and the saturated steam goes through the shell layer and the waste acid goes through the tube layer. It should be understood by those skilled in the art that the higher the concentration of the waste acid, the higher the preheating temperature required. This is because the higher the concentration of the waste acid, the greater the amount of waste acid reuse, the less the mass fraction of 98% concentrated sulfuric acid is consumed, and the less dilution heat is released. Therefore, more heat needs to be supplemented to achieve a better reaction temperature and reaction rate.

[0037] When the waste acid is preheated by saturated steam, if the preheating temperature is too low, the acidolysis rate of the titanium concentrate will be low, and if the preheating temperature is too high, the saturated steam consumption will be large, and the acidolysis reaction effect may decrease. Therefore, the present invention establishes a mathematical relationship between the waste acid preheating temperature and the waste acid concentration, so that different concentrations of waste acid correspond to different preheating temperatures, thereby reducing the consumption of saturated steam and ensuring the acidolysis reaction effect. Since indirect heating will not cause the steam condensate to enter the reaction acid, the present invention preheats the waste acid to a certain temperature by heating other than saturated steam (indirect preheating), thereby ensuring that the acid concentration of the titanium concentrate acidolysis reaction will not be reduced, and at the same time overcomes the technical difficulties of low acidolysis reaction temperature and slow acidolysis reaction rate caused by lack of heat in the waste acid-induced continuous acidolysis of titanium concentrate, thereby achieving an improvement in the acidolysis rate of titanium concentrate and the level of waste acid reuse.

[0038] In one embodiment, after step S33, the following steps are also included: S34, leaching the acid-decomposed solid phase to obtain a leached titanium liquid.

[0039] S35, reducing the leached titanium liquid with iron powder to obtain reduced leached titanium liquid.

[0040] S36. Add a flocculant to the reduced leached titanium solution for sedimentation treatment.

[0041] In one embodiment, in step S34, the concentration of titanium dioxide in the leached titanium solution is 125 g / L to 135 g / L. In step S35, the concentration of trivalent titanium in the leached titanium solution after reduction is 1 g / L to 2 g / L. In step S36, the ratio of the mass of the added flocculant to the mass of titanium dioxide in the leached titanium solution after reduction is 0.25‰, and the flocculant is polyacrylamide.

[0042] The present invention also provides a method for preparing titanium dioxide, which includes the above-mentioned method for improving the acid hydrolysis performance of titanium concentrate.

[0043] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0044] Example 1 Titanium concentrate (the proportions of ilmenite, pyroxene and feldspar in the titanium concentrate are 89.6wt%, 3.1wt% and 0.8wt% respectively) is prepared using the iron tailings of vanadium-titanium magnetite as raw material. 34.0kg / t of industrial-grade sulfuric acid and 7.8kg / t of collector butyl xanthate are added to the titanium concentrate by flotation to beneficiate the titanium concentrate to obtain upgraded titanium concentrate (the proportions of ilmenite, pyroxene and feldspar in the upgraded titanium concentrate are 95.0wt%, 1.4wt% and 0.3wt% respectively). The upgraded titanium concentrate is dried to a moisture content of 0.5% and ground to a 325-mesh sieve residue of 1%.

[0045] The upgraded titanium concentrate is premixed with 98% concentrated sulfuric acid to obtain an acid ore premix. Waste acid with a sulfuric acid concentration of 20wt% is provided, and the waste acid is preheated to 25.76°C with saturated steam at a temperature of 140°C. The preheated waste acid is mixed with the acid ore premix for continuous acid hydrolysis reaction to obtain an acid hydrolysis solid phase, and the acid hydrolysis solid phase is taken to measure the acid hydrolysis rate. The mass ratio of the reaction acid to the upgraded titanium concentrate is 1.60, the concentration of the reaction acid is 83.0wt%, and the aging time is 1h.

[0046] The acid-lyzed solid phase was leached to obtain a leached titanium solution with a titanium dioxide concentration of 125 g / L. The leached titanium solution was reduced using iron powder, and the trivalent titanium concentration in the reduced leached titanium solution was controlled to be 1 g / L. At the end of the reduction, polyacrylamide, a flocculant, was added, and the ratio of the mass of the added polyacrylamide to the mass of titanium dioxide in the reduced leached titanium solution was 0.25‰. The mixture was stirred for 10 minutes, placed in a sedimentation tank, and settled for 4 hours. 100 mL of the supernatant was taken to measure its filtration time and solid content, and then the normal sulfuric acid method titanium dioxide process was used for production (see Figure 2 ), count the amount of recycled waste acid per ton of titanium dioxide, and finally measure the whiteness L value, a value, brightness and tinting power of titanium dioxide.

[0047] Example 2 Titanium concentrate (the proportions of ilmenite, pyroxene and feldspar in the titanium concentrate are 89.6wt%, 3.1wt% and 0.8wt% respectively) is prepared using the iron tailings of vanadium-titanium magnetite as raw material. 37.0kg / t of industrial-grade sulfuric acid and 8.5kg / t of collector butyl xanthate are added to the titanium concentrate by flotation to beneficiate the titanium concentrate to obtain upgraded titanium concentrate (the proportions of ilmenite, pyroxene and feldspar in the upgraded titanium concentrate are 96.2wt%, 1.1wt% and 0.2wt% respectively). The upgraded titanium concentrate is dried to a moisture content of 0.4% and ground to a 325-mesh sieve residue of 2%.

[0048] The upgraded titanium concentrate was premixed with 98% concentrated sulfuric acid to obtain an acid ore premix. Waste acid with a sulfuric acid concentration of 40wt% was provided, and the waste acid was preheated to 93.76°C with saturated steam at a temperature of 150°C. The preheated waste acid was mixed with the acid ore premix for continuous acid hydrolysis reaction to obtain an acid hydrolysis solid phase, and the acid hydrolysis solid phase was taken to measure the acid hydrolysis rate. The mass ratio of the reaction acid to the upgraded titanium concentrate was 1.61, the concentration of the reaction acid was 83.3wt%, and the aging time was 2h.

[0049] The acid-lyzed solid phase was leached to obtain a leached titanium liquid with a titanium dioxide concentration of 125 g / L. The leached titanium liquid was reduced with iron powder, and the trivalent titanium concentration in the reduced leached titanium liquid was controlled to be 1.0 g / L. At the end of the reduction, polyacrylamide, a flocculant, was added, and the ratio of the mass of the added polyacrylamide to the mass of titanium dioxide in the reduced leached titanium liquid was 0.25‰. The mixture was stirred for 10 minutes and placed in a sedimentation tank for 4 hours. 100 mL of the supernatant was taken to measure its filtration time and solid content. The normal sulfuric acid method titanium dioxide process was followed for production, and the amount of waste acid recycled per ton of titanium dioxide was counted. Finally, the whiteness L value, a value, brightness and tinting power of titanium dioxide were measured.

[0050] Example 3 Titanium concentrate (the proportions of ilmenite, pyroxene and feldspar in the titanium concentrate are 89.6wt%, 3.1wt% and 0.8wt% respectively) is prepared using the iron tailings of vanadium-titanium magnetite as raw material. 40.0kg / t of industrial-grade sulfuric acid and 9.5kg / t of collector butyl xanthate are added to the titanium concentrate by flotation to beneficiate the titanium concentrate to obtain upgraded titanium concentrate (the proportions of ilmenite, pyroxene and feldspar in the upgraded titanium concentrate are 98.0wt%, 0.5wt% and 0wt% respectively). The upgraded titanium concentrate is dried to a moisture content of 0.3% and ground to a 325-mesh sieve residue of 3%.

[0051] The upgraded titanium concentrate was premixed with 98% concentrated sulfuric acid to obtain an acid ore premix. Waste acid with a sulfuric acid concentration of 60wt% was provided, and the waste acid was preheated to 161.76℃ with saturated steam at a temperature of 250℃. The preheated waste acid was mixed with the acid ore premix for continuous acid hydrolysis reaction to obtain an acid hydrolysis solid phase, and the acid hydrolysis solid phase was taken to measure the acid hydrolysis rate. The mass ratio of the reaction acid to the upgraded titanium concentrate was 1.62, the concentration of the reaction acid was 83.5wt%, and the aging time was 3h.

[0052] The acid-lyzed solid phase was leached to obtain a leached titanium liquid with a titanium dioxide concentration of 125g / L. The leached titanium liquid was reduced with iron powder, and the trivalent titanium concentration in the reduced leached titanium liquid was controlled to be 1g / L. At the end of the reduction, polyacrylamide, a flocculant, was added, and the ratio of the mass of the added polyacrylamide to the mass of titanium dioxide in the reduced leached titanium liquid was 0.25‰. The mixture was stirred for 10 minutes and placed in a sedimentation tank for 4 hours. 100mL of the supernatant was taken to measure its filtration time and solid content. The normal sulfuric acid method titanium dioxide process was then used for production. The amount of waste acid recycled per ton of titanium dioxide was counted, and finally the whiteness L value, a value, brightness and tinting power of titanium dioxide were measured.

[0053] Comparative Example 1 The main difference between Comparative Example 1 and Example 1 is that Comparative Example 1 does not perform beneficiation treatment on the titanium concentrate, and Comparative Example 1 uses water to induce a continuous acid hydrolysis reaction, and does not recycle the waste acid.

[0054] Titanium concentrate (the proportions of ilmenite, pyroxene and feldspar in the titanium concentrate are 89.6wt%, 3.1wt% and 0.8wt% respectively) is prepared using the iron tailings of vanadium-titanium magnetite as raw material. The titanium concentrate is dried to a moisture content of 0.5% and ground to a 325 mesh sieve residue of 1%.

[0055] Titanium concentrate was premixed with 98% concentrated sulfuric acid to obtain an acid ore premix. Water was mixed with the acid ore premix, and a continuous acid hydrolysis reaction was initiated by water to obtain an acid hydrolysis solid phase, and the acid hydrolysis solid phase was taken to measure the acid hydrolysis rate. The mass ratio of the reaction acid to the titanium concentrate was 1.60, the concentration of the reaction acid was 83.0wt%, and the aging time was 1h.

[0056] The acid-lyzed solid phase was leached to obtain a leached titanium liquid with a titanium dioxide concentration of 125g / L. The leached titanium liquid was reduced with iron powder, and the trivalent titanium concentration in the reduced leached titanium liquid was controlled to be 1g / L. At the end of the reduction, polyacrylamide, a flocculant, was added, and the ratio of the mass of the added polyacrylamide to the mass of titanium dioxide in the reduced leached titanium liquid was 0.25‰. The mixture was stirred for 10 minutes and placed in a sedimentation tank for 4 hours. 100mL of the supernatant was taken to measure its filtration time and solid content. The normal sulfuric acid method titanium dioxide process was then used for production. The amount of waste acid recycled per ton of titanium dioxide was counted, and finally the whiteness L value, a value, brightness and tinting power of titanium dioxide were measured.

[0057] Comparative Example 2 Compared with Example 2, Comparative Example 2 performs beneficiation treatment on titanium concentrate, but Comparative Example 2 uses water to induce continuous acid hydrolysis reaction and does not recycle waste acid.

[0058] Titanium concentrate (the proportions of ilmenite, pyroxene and feldspar in the titanium concentrate are 89.6wt%, 3.1wt% and 0.8wt% respectively) is prepared using the iron tailings of vanadium-titanium magnetite as raw material. 37.0kg / t of industrial-grade sulfuric acid and 8.5kg / t of collector butyl xanthate are added to the titanium concentrate by flotation to beneficiate the titanium concentrate to obtain upgraded titanium concentrate (the proportions of ilmenite, pyroxene and feldspar in the upgraded titanium concentrate are 96.2wt%, 1.1wt% and 0.2wt% respectively). The upgraded titanium concentrate is dried to a moisture content of 0.4% and ground to a 325-mesh sieve residue of 2%.

[0059] The upgraded titanium concentrate was premixed with 98% concentrated sulfuric acid to obtain an acid ore premix. Water was mixed with the acid ore premix, and a continuous acid hydrolysis reaction was initiated by water to obtain an acid hydrolysis solid phase, and the acid hydrolysis solid phase was taken to measure the acid hydrolysis rate. The mass ratio of the reaction acid to the upgraded titanium concentrate was 1.61, the concentration of the reaction acid was 83.3wt%, and the aging time was 2h.

[0060] The acid-lyzed solid phase was leached to obtain a leached titanium liquid with a titanium dioxide concentration of 125 g / L. The leached titanium liquid was reduced with iron powder, and the trivalent titanium concentration in the reduced leached titanium liquid was controlled to be 1.0 g / L. At the end of the reduction, polyacrylamide, a flocculant, was added, and the ratio of the mass of the added polyacrylamide to the mass of titanium dioxide in the reduced leached titanium liquid was 0.25‰. The mixture was stirred for 10 minutes and placed in a sedimentation tank for 4 hours. 100 mL of the supernatant was taken to measure its filtration time and solid content. The normal sulfuric acid method titanium dioxide process was followed for production, and the amount of waste acid recycled per ton of titanium dioxide was counted. Finally, the whiteness L value, a value, brightness and tinting power of titanium dioxide were measured.

[0061] Comparative Example 3 The main difference between Comparative Example 3 and Example 3 is that Comparative Example 3 does not perform beneficiation treatment on the titanium concentrate, and Comparative Example 3 uses water to induce a continuous acid hydrolysis reaction, and does not recycle the waste acid.

[0062] Titanium concentrate (the proportions of ilmenite, pyroxene and feldspar in the titanium concentrate are 89.6wt%, 3.1wt% and 0.8wt% respectively) is prepared using the iron tailings of vanadium-titanium magnetite as raw material. The titanium concentrate is dried to a moisture content of 0.3% and ground to a 325-mesh sieve residue of 3%.

[0063] Titanium concentrate was premixed with 98% concentrated sulfuric acid to obtain an acid ore premix. Water was mixed with the acid ore premix, and a continuous acid hydrolysis reaction was initiated by water to obtain an acid hydrolysis solid phase, and the acid hydrolysis solid phase was taken to measure the acid hydrolysis rate. The mass ratio of the reaction acid to the titanium concentrate was 1.62, the concentration of the reaction acid was 83.5wt%, and the aging time was 3h.

[0064] The acid-lyzed solid phase was leached to obtain a leached titanium liquid with a titanium dioxide concentration of 125g / L. The leached titanium liquid was reduced with iron powder, and the trivalent titanium concentration in the reduced leached titanium liquid was controlled to be 1g / L. At the end of the reduction, polyacrylamide, a flocculant, was added, and the ratio of the mass of the added polyacrylamide to the mass of titanium dioxide in the reduced leached titanium liquid was 0.25‰. The mixture was stirred for 10 minutes and placed in a sedimentation tank for 4 hours. 100mL of the supernatant was taken to measure its filtration time and solid content. The normal sulfuric acid method titanium dioxide process was then used for production. The amount of waste acid recycled per ton of titanium dioxide was counted, and finally the whiteness L value, a value, brightness and tinting power of titanium dioxide were measured.

[0065] The relevant results of Examples 1-3 and Comparative Examples 1-3 are shown in Table 1.

[0066] Table 1 Comparison of results of examples and comparative examples

[0067] From the comparison between Examples 1-3 and Comparative Examples 1-3, it can be seen that the method of the present invention can improve the acid hydrolysis rate of titanium concentrate produced by sulfuric acid process titanium dioxide and the amount of waste acid recycled per ton of titanium dioxide, the solid content of the titanium liquid is reduced after sedimentation, the filtration speed is increased, and the quality of titanium dioxide products such as whiteness L value, b value, brightness and tinting power are all improved. In summary, the present invention can not only improve the acid hydrolysis rate of titanium concentrate, titanium liquid sedimentation, filtration speed and waste acid recycling level, but also improve the whiteness L value, b value, brightness and tinting power of titanium dioxide.

[0068] It should be particularly pointed out that the various components or steps in the above-mentioned embodiments can be cross-linked, replaced, added, or deleted with each other. Therefore, the combinations formed by these reasonable arrangements and combinations should also fall within the scope of protection of the present invention, and the scope of protection of the present invention should not be limited to the embodiments.

[0069] A person skilled in the art should understand that the discussion of any of the above embodiments is only exemplary and is not intended to imply that the scope of the disclosure of the embodiments of the present invention (including the claims) is limited to these examples; under the concept of the embodiments of the present invention, the technical features in the above embodiments or different embodiments can also be combined, and there are many other changes in different aspects of the embodiments of the present invention as described above, which are not provided in detail for the sake of simplicity. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the embodiments of the present invention should be included in the protection scope of the embodiments of the present invention.

Claims

1. A method for improving the acid hydrolysis performance of titanium concentrate, characterized in that: The method comprises the following steps: S10. Provide titanium concentrate; S20, performing beneficiation treatment on the titanium concentrate, so that the proportion of ilmenite in the titanium concentrate is increased, and the proportion of pyroxene and feldspar in the titanium concentrate is reduced, so as to obtain an upgraded titanium concentrate; S30, continuously performing acid hydrolysis treatment on the upgraded titanium concentrate.

2. The method according to claim 1, characterized in that: In step S20, The titanium concentrate is beneficiated by flotation process using 98% by mass industrial grade sulfuric acid and collector, wherein the amount of industrial grade sulfuric acid added is 34.0 kg / t to 40.0 kg / t of titanium concentrate, and the amount of collector added is 7.8 kg / t to 9.5 kg / t of titanium concentrate.

3. The method according to claim 1, characterized in that In step S10, The proportion of ilmenite in the titanium concentrate is <90wt%, the proportion of pyroxene in the titanium concentrate is 3.1wt%, and the proportion of feldspar in the titanium concentrate is 0.8wt%.

4. The method according to claim 3, characterized in that: In step S20, The proportion of ilmenite in the upgraded titanium concentrate is 95.0wt% to 98.0wt%, the proportion of pyroxene in the upgraded titanium concentrate is 0.5wt% to 1.4wt%, and the proportion of feldspar in the upgraded titanium concentrate is 0wt% to 0.3wt%.

5. The method according to claim 1, characterized in that In step S30, the continuous acid hydrolysis process includes the following steps: S31, premixing the upgraded titanium concentrate with concentrated sulfuric acid to obtain an acid ore premix; S32, providing waste acid, and preheating the waste acid to obtain preheated waste acid, the waste acid preheating temperature T = -32.24 + 240 × C + (10 ° C ~ 50 ° C), wherein C is the mass concentration of sulfuric acid in the waste acid; S33, mixing the preheated waste acid with the acid-ore premix, initiating a continuous acidolysis reaction with the waste acid, and obtaining an acidolysis solid phase after the reaction, wherein the preheated waste acid is mixed with the concentrated sulfuric acid in step S31 to form a reaction acid.

6. The method according to claim 5, characterized in that Before step S31, the upgraded titanium concentrate is dried and ball-milled, and the moisture content of the upgraded titanium concentrate after drying is ≤0.5%, and the particle size of the upgraded titanium concentrate is 1% to 3% of the residue on a 325-mesh sieve; In step S31, the mass fraction of concentrated sulfuric acid is 98%; In step S32, the concentration of sulfuric acid in the waste acid is 20 wt% to 60 wt%; In step S33, the mass ratio of the reaction acid to the upgraded titanium concentrate is 1.60-1.62, the concentration of the reaction acid is 83.0wt%-83.5wt%, and the aging time is 1h-3h.

7. The method according to claim 5, characterized in that In step S32, the waste acid is indirectly preheated by saturated steam, and the temperature of the saturated steam is 140°C to 250°C.

8. The method according to claim 5, characterized in that After step S33, the following steps are also included: S34, leaching the acid-decomposed solid phase to obtain a leached titanium liquid; S35, reducing the leached titanium liquid with iron powder to obtain a reduced leached titanium liquid; S36. Add a flocculant to the reduced leached titanium solution for sedimentation treatment.

9. The method according to claim 8, characterized in that In step S34, the concentration of titanium dioxide in the leached titanium solution is 125 g / L to 135 g / L; In step S35, the concentration of trivalent titanium in the leached titanium solution after reduction is 1 g / L to 2 g / L; In step S36, the ratio of the mass of the added flocculant to the mass of titanium dioxide in the reduced leached titanium solution is 0.25‰.

10. A method for preparing titanium dioxide, characterized in that: The titanium dioxide preparation method includes the method for improving the acid hydrolysis performance of titanium concentrate according to any one of claims 1 to 9.